The economists' hour [compact disc, unabridged] : false prophets, free markets, and the fracture of society - Appelbaum, Binyamin (Hachette Audio, 2019)
Before the 1960s, professional economists played little role in American politics. As Binyamin Appelbaum shows in this masterful work of history, when the post-World War II boom began to sputter, economists rose in influence and power. Over the past half-century, they have moved to center stage, running the Federal Reserve and the Treasury, overseeing federal regulation, advising presidents to cut taxes and to restrain government spending. From the mid-1950s to the mid-1970s, the number of economists on the federal payroll roughly tripled. Their fundamental belief? That government should stop trying to manage the economy. Their guiding principle? That unfettered markets are the only way to deliver steady growth, and to ensure that all Americans share in the benefits. The result? Those economists and their ideas have reshaped the modern world, curbing government, unleashing corporations, and clearing the way for globalization.